The Developmental Status of Abadan, Khorramshahr and Shadegan Terms of Health Indices Using Numerical Taxonomy Model - Mohammad Mahboubi; Babak Rastegarimehr; Mohammad Sajedinejad; Atefeh Zahedi; Najiballah Baeradeh; Leila Rezaei; Ali Ebrazeh (Golestan University of Medical Sciences, 2020)
Background: One of the main pillars of sustainable development is health and wellness which is an integral part of improving the quality of life. Lack of hygiene facilities and human resources and their inadequate distribution in urban and rural areas are major problems in providing health services in third world countries. The main and important reasons for inequalities in the distribution of health sector resources include inappropriate and poor budget allocation to the health sector, inadequate and long-term planning. This study was conducted to determine the degree of development of Abadan, Khorramshahr and Shadegan cities in terms of health indicators using numerical taxonomy model. Methods: This descriptive study was conducted in 3 cities of Abadan, Khorramshahr and Shadegan in Khuzestan province in 2016. The data collection tool was a checklist containing information needed to calculate 15 health indices that were collected from Abadan Medical School Deputy of Health. The numerical taxonomy of these cities was evaluated in terms of degree of development of health indicators. Results: According to the values of the upper and lower limits of homogeneity distance and the values of the shortest distance between cities, it was found that all cities (regions) were homogeneous and were in the same group. Finally, the results showed that Abadan is considered to be developed (0.47), Shadegan under developed (0.78) and Khorramshahr undeveloped (0.81). Conclusion: Regarding the results obtained for improving the health status and managing the health sector, it is suggested that a comprehensive development-based program to be developed for reducing gaps and inequalities in terms of health indicators and to pay specific attention to the main development indicators of health care system based on population in each region.